Strategi KBRI Manila Pada Diplomasi Ekonomi Sektor Perdagangan Tahun 2022 - Susanto, Fathima Aulia Vasya; Nur Azizah (Universitas Cenderawasih, 2024)
This research discusses the strategies of the Embassy of the Republic of Indonesia in Manila, the Philippines, in increasing Indonesian trade to the Philippines in 2022. The movement of Indonesian trade to the Philippines has experienced fluctuation from 2018 to 2021. In 2022, there was a significant increase after the pandemic considering the trade stagnation in 2018-2019 in a stable international condition. This research using descriptive-qualitative research method, found that strategy of the Indonesian Embassy in Manila to enhance trade through trade promotion, business matching, business forums, and export cooperation facilitation was planned using a SWOT analysis. This analysis shows that trade promotion and business forums leverage the strengths of diplomatic networks and market expansion opportunities, while business matching and export facilitation are optimized to address weaknesses such as bureaucracy and cultural differences. Threats from global economic instability and market competition are identified to ensure the right strategies are implemented to achieve trade objectives in 2022. In 2022, the Indonesian Embassy in Manila successfully increased Indonesian trade to the Philippines by 50%, up by 4.18% from 2021, through the successful implementation of economic diplomacy strategies in the trade sector. KEYWORDSEconomic Diplomacy; Indonesia; Philippine; Trade